Penguatan Halal Value Chain pada Klaster Makanan dan Minuman di Indonesia - Rudi Purnama; Indra; Rininta Nurrachmi (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2024)
This research analyzes the strengthening of the halal value chain in the halal food and beverage cluster in Indonesia as a strategy to encourage Indonesia to become a world center for halal production based on Porter's value chain theory. Primary activities and supporting activities must produce added value in every process of producing halal products. The added value generated from each link in the chain can increase competitive advantage so that halal food and beverage products in Indonesia are guaranteed to be 100% halal and these products have high competitiveness. This research design is exploratory qualitative with a field study approach. Primary data sources were obtained by conducting structured in-depth interviews and making direct and indirect observations, while secondary data were obtained from documentation studies, national and international journals, books, online media, etc. The data analysis technique uses the Miles and Huberman theory with stages of data reduction, data presentation, and drawing conclusions or verification. The research results concluded that the halal value chain in the food and beverage cluster in Indonesia has not produced maximum added value to achieve competitive advantage in increasing product competitiveness.